Incidence, Severity and Prognosis Associated with Hypernatremia in Dogs and Cats. (May 2015) - Ueda, Y.; Hopper, K.; Epstein, S.E.
<x xml:space="preserve">Abstract</x> Background Hypernatremia has been associated with substantial morbidity and death in human patients. The incidence and importance of hypernatremia in dogs and cats has not been determined. Hypothesis/Objectives To describe the incidence of and prognosis associated with hypernatremia in dogs and cats at a university teaching hospital. Animals A total of 16, 691 dogs and 4, 211 cats with measured blood or serum sodium concentration. Methods Retrospective study. Medical records of animals with a blood or serum sodium concentration measured during a 60‐month period were reviewed to determine the severity of hypernatremia and its associated case fatality rate. Cases with moderate (11–15 mmol/L above the reference range) or severe hypernatremia (≥16 mmol/L above the reference range) were further reviewed. Results A total of 957 dogs (5.7%) and 338 cats (8.0%) were diagnosed with hypernatremia. Case fatality rates of dogs and cats with hypernatremia was 20.6 and 28.1%, respectively compared to 4.4 and 4.5% with a normal blood or serum sodium concentration (P < .0001). The magnitude of hypernatremia was linearly associated with a higher case fatality rate (P < .0001). Hypernatremia was associated with a higher case fatality rate than hyponatremia. Among the animals with moderate or severe hypernatremia, 50% of dogs and 38.5% of cats presented with community‐acquired hypernatremia, and 50% of dogs and 61.5% of cats developed hospital‐acquired hypernatremia. Conclusions and clinical importance Hypernatremia was found infrequently in this population but was associated with increased case fatality rates in dogs and cats. Presence and severity of hypernatremia might be useful as a prognostic indicator.